2016
DOI: 10.1210/jc.2016-2620
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Sonographic, and Pathological Characteristics of RAS-Positive Versus BRAF-Positive Thyroid Carcinoma

Abstract: BRAF-positive malignant nodules most often demonstrate worrisome sonographic features and are frequently associated with positive or suspicious Bethesda cytology. In contrast, RAS-positive malignancy most often demonstrates indolent sonographic features and more commonly associates with lower risk, "indeterminate" cytology. Because BRAF and RAS mutations are the most common molecular perturbations associated with well-differentiated thyroid cancer, these findings may assist with improved preoperative risk asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
4
14
0
Order By: Relevance
“…Interestingly, we observed that FNAs with RAS and RAS ‐like mutations were obtained from nodules that were larger than those harboring BRAF V600E and BRAF ‐like alterations—a finding in line with other experiences suggesting that RAS ‐mutated nodules grow at a faster rate …”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, we observed that FNAs with RAS and RAS ‐like mutations were obtained from nodules that were larger than those harboring BRAF V600E and BRAF ‐like alterations—a finding in line with other experiences suggesting that RAS ‐mutated nodules grow at a faster rate …”
Section: Discussionsupporting
confidence: 91%
“…A recent trial demonstrated that among 60 patients with the BRAF mutation, 90% had LVI. In another study, among 71 BRAF(+) PTC patients, 46% had LVI, and the BRAF mutation was found to be a statistically significant risk factor for LVI in these PTC patients [45]. Our study is the largest clinical series investigating the association between the presence of LVI and BRAF mutation in PTC patients.…”
Section: Discussionmentioning
confidence: 53%
“…The BRAF gene mutation is found in approximately 45% of thyroid cancer patients and most studies indicate that the BRAF mutation is a poor prognostic factor in these patients. However, recent studies on the BRAF mutation status in PTC patients showed conflicting results; furthermore, limited data exist on the association between the BRAF mutation and LVI in PTC patients [44,45]. A recent trial demonstrated that among 60 patients with the BRAF mutation, 90% had LVI.…”
Section: Discussionmentioning
confidence: 99%
“…MAP kinase, PI3K, and V600E mutation in BRAF oncogene are common features in melanoma and TC [ 52 , 53 ]. On the cellular level, RAS and BRAF mutations, but not ARAF or CRAF mutations, play significant roles in the ERK signaling pathway [ 54 , 55 , 56 ]. For example, ERK accumulates in the nucleus following stimulation by mitogenic signals.…”
Section: Dysregulation Of Nucleocytoplasmic Transport In Melanoma mentioning
confidence: 99%